Macroeconomic Indicators And Sukuk Market Performance In Selected Oic Economies - Nursilah Ahmad; Syazwani Abd. Rahim; Nurul Atika Azzan; Asma Abdul Rahman (Institute for Research and Community Empowerment (IRCE), 2024)
Volume 15 No:2 (Page: 1-22)